Improving MSME perfomance through competences and entrepreneurial characteristics - Rr. Lulus Prapti Nugroho Setiasih Surjanti; Edy Mulyantomo; Dian Triyani; Emaya Kurniawati (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to analyze the influence of human resource competence, management competence, and entrepreneurial competence on the performance of Micro, Small and Medium Enterprises (MSMEs), moderated by entrepreneurial characteristics. Methodology: The research was conducted on 95 MSME actors from the "Cethik Geni" group in Semarang. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS). Results: This study examines the influence of human resource, management, and entrepreneurial competencies on MSME performance, as well as the moderating role of entrepreneurial characteristics, within the Gerai Kopini (Cethik Geni) MSME Group in Semarang City. The findings indicate that all three competencies positively and significantly enhance MSME performance. Entrepreneurial characteristics strengthen the effect of management competency on performance but do not moderate the influence of human resource and entrepreneurial competencies. Conclusions: This study concludes that strengthening human resource, management, and entrepreneurial competencies is essential for improving MSME performance. Entrepreneurial characteristics play a supportive role by enhancing the effectiveness of management competency, although they do not function as a moderating factor for all competency performance relationships. Limitations: This study is limited to the Cethik Geni MSME Group in Semarang, restricting generalizability. The moderating role of entrepreneurial characteristics was inconsistent, and unexamined contextual and qualitative factors such as leadership, motivation, and teamwork may affect the results. Contribution: Future research is recommended to expand the scope of respondents to various MSME sectors and regions to increase the generalizability of the findings. Furthermore, the research model must include contextual variables such as organizational culture, business environment, and leadership style as moderators or mediators.